Analisis Peran Pembiayaan KUR Mikro dalam Mendukung Peningkatan Daya Saing UMKM di Era Digital: Studi Kasus di Bank Syariah Indonesia KCP Sumedang Tanjungsari 2 - Rijanti Rahayu Maulani; Ridwan Effendi (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
Rapid technological developments create opportunities for businesses to scale their businesses. Sharia Micro KUR is a step toward optimizing working capital and investment in accordance with sharia principles. This study aims to analyze the role of Micro KUR financing, outline strategies for utilizing Micro KUR financing in the digital era, and identify challenges in distributing and utilizing Micro KUR to increase the competitiveness of MSMEs. This study uses a qualitative approach and descriptive methods with primary and secondary data sources through observation, interviews with Micro staff, and literature review of articles related to MSMEs in the Digital Era. The analysis shows that Micro KUR financing is a solution for economic development in Indonesia, serving halal MSMEs facing capital challenges. Sharia Micro KUR can be utilized by MSMEs to meet their capital needs as an alternative to adopting digital marketing technology through social media. However, behind the utilization of Micro KUR, there are significant challenges in distributing BSI and utilizing MSMEs. Suggestions for other researchers include applying a quantitative approach with statistical data analysis regarding the relationship between the use of Sharia Micro KUR and increasing the competitiveness of MSMEs in the digital era.